Biogas production from vegetable and fruit wastes combined with manure from pigs or buffaloes : - Sopheap, Yen (Can Tho University, 2017)
A series of experiments was carried out to determinethe effect on biogas production when manure from buffalos and pigs was supplemented with : (i) vegetable waste; (ii) fruit waste; (iii) water spinach (Ipomoea aquatica); or (iv) Siam weed (chromalaena odorata).